The Urgency of Strengthening International Criminal Justice in Combating Impunity of Perpetrators of International Crimes: The Perspective of the 1998 Rome Statute - Sanddy Pratama Putra; Hadi Purnomo (TGO Journal of Community Development, 2026)
This study aims to analyze the urgency of strengthening international criminal justice in overcoming impunity for international criminals and to examine the effectiveness of the implementation of the 1998 Rome Statute as an instrument of international law in realizing criminal accountability. The research method used is normative juridical research with a statute approach, a conceptual approach, and a case approach. The legal materials used consist of primary, secondary, and tertiary legal materials that are qualitatively analyzed through legal interpretation. The results of the study show that the Rome Statute of 1998 has provided a comprehensive legal basis for the prosecution of international criminals through the application of the principles of complementarity, individual criminal responsibility, and international cooperation. However, the effectiveness of international criminal justice still faces various obstacles in the form of political intervention, limited jurisdiction, non-compliance of states with cooperation obligations, and the lack of optimal harmonization of national law with the provisions of the Rome Statute. Therefore, strengthening the ICC institution, increasing the commitment of countries in implementing international obligations, and expanding the ratification of the Rome Statute are strategic steps to reduce impunity and realize a more effective, fair, and just international criminal justice system.